Intense relationship of blood pressure and stadium of chronic kidney disease at early diagnosis - Putra, Wisnu Pratama; Tania, Putu Oky Ari; Njoto, Ibrahim; Suryawati, Sianny (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Chronic kidney disease (CKD) is a pathological stage with multiple causes that is characterised by a very high level of urea in the body because the kidneys are unable to balance the metabolism of fluids and electrolytes. Previous research has demonstrated that high blood pressure is one of the causes of chronic kidney disease. This study was conducted to determine the relationship between blood pressure and the initial stage of chronic kidney disease. observational study of Ninety patients with chronic kidney disease (CKD) at the RSUD Dr. Soeroto, Ngawi participated in this cross-sectional. Subjects were required to have CKD stages I-IV, high blood pressure, to be hospitalised for the first time at RSUD dr Soeroto, Ngawi, and to have never been treated for hypertension. This study employed the Spearman rank test, which was analysed by SPSS (p<0.05). 64.5% of patients with chronic kidney disease have reached stage V. In contrast, 47.8% of patients with chronic kidney disease have stage 2 hypertension. The Spearman Rank test revealed a p-value of 0.000 (<0.05) between blood pressure and the stage of chronic kidney disease at the time of initial diagnosis in patients with chronic kidney disease. The correlation coefficient has a value of 0.638, making it a strong correlation. There is a strong correlation between blood pressure and the stage of chronic kidney disease at the initial diagnosis of chronic kidney disease patients at the RSUD Dr. Soeroto, Ngawi.